Direct Top‐Down Fabrication of Large‐Area Graphene Arrays by an In Situ Etching Method. (12th June 2015) - Geng, Dechao; Wang, Huaping; Wan, Yu; Xu, Zhiping; Luo, Birong; Xu, Jie; Yu, Gui
<x xml:space="preserve">Abstract</x> Large‐area aligned hexagonal graphene arrays are directly fabricated by an in situ etching method. With precise control over the size, shape, and orientation, the technique allows hydrogen to be employed as an effective etchant on chemical vapor deposited graphene and leads to ordered graphene nanostructures. This direct top‐down approach can enable atomically precise construction of integrated devices from single graphene sheets with a wide range of technological applications.